Meaning and learning fractions: analysis of learning barriers from a mathematics teacher's perspective - Alsulami, Naif Mastoor; Isnawan, Muhamad Galang; Bahri, Samsul; Pakhrurrozi, Imam; Santosa, Farah Heniati (Polyhedron International Journal in Mathematics Education, 2023)
Converting mixed numbers into common fractions is one of the formula problems in learning fractions which is a problem in learning. However, not many studies have examined this conversion. In addition, there are not many studies that try to provide solutions to the conversion problem. Therefore, this study aims to identify the types of learning barriers students experience when converting mixed numbers into common fractions and provide alternative solutions to minimize these learning barriers. The research design used to achieve this goal is didactical design research (DDR). DDR was chosen because it uses the results of identifying types of learning barriers to develop didactic designs in learning fractions. The participants in this study were math teachers with 26 years of age and less than 5 years of teaching experience. The main instrument in this study was the researcher using several additional instruments, such as fraction comprehension tests, interview guides, and didactic designs. The data was then analyzed using qualitative data analysis. The results of the study revealed that students indicated that they experienced learning difficulties with different types of epistemological obstacles because they rarely start learning with everyday life problems. The solution offered in the didactical design is the use of the problem as an initial situation in learning which students will then respond to in the form of a didactical situation. The recommendations offered in this study are the implementation of the didactic design itself.